Mineralization of Triadimefon Fungicide in Water by Electro-Fenton and Photo Electro-Fenton - Ureta-Zanartu, M; Salazar-Gonzalez, R (2012)
The complete mineralization of the conazole fungicide triadimefon in water at pH 3 using electrochemical advanced oxidation processes, electro-Fenton and photo electro-Fenton, was achieved. The electrochemical system consisted of a one-compartment electrochemical cell of 100 mL provided with a glassy carbon mesh electrode (cathode) and a concentric outer steel mesh as anode. The electrolysis was realized at constant current. The most remarkable features are as follows: (1) photo electro-Fenton process reaches a complete mineralization of triadimefon after 2 h of electrolysis with respect to electro-Fenton method; and (2) 4-chlorophenol, hydroquinone, carboxylic acids, and inorganic ions were detected as intermediates of degradation processes, which end with the complete mineralization of triadimefon to CO 2?+?H 2O. (3) A reaction pathway for the oxidation of triadimefon fungicide by hydroxyl radicals that accounts for almost all detected intermediates is proposed. © 2012 Springer Science+Business Media B.V.